Analysis of Socio-Ecological Values in Elementary School Science and Social Studies Textbooks of the Merdeka Curriculum - Isvina Unaizahroya; Prasetyo Adi Nugroho; Zetti Finali (The Future of Education Journal, 2025)
The integration of Natural Sciences (IPA) and Social Studies (IPS) into a single subject (IPAS) within the Merdeka Curriculum aims to foster a holistic understanding of phenomena. However, the implementation of this integration in textbooks often faces challenges regarding coherence. This study aims to critically analyze the content of socio-ecological values in Grade III IPAS textbooks, specifically examining how the narrative connects human social dynamics with environmental sustainability. Using a qualitative content analysis method with a Socio-Ecological Systems (SES) framework, this study evaluated three key indicators: system interdependence, adaptive capacity, and the integration of diverse knowledge systems. The data source was the official IPAS textbook published by the Ministry of Education, Culture, Research, and Technology (2022). The findings reveal that material segregation persists; scientific and social topics are predominantly treated in silos. Furthermore, local wisdom is often reduced to aesthetic artifacts rather than presented as conservation strategies, and narratives concerning adaptive capacity against environmental changes are minimal. The study concludes that the current textbooks have not fully succeeded in bridging the human-nature gap, necessitating pedagogical intervention by teachers to cultivate critical environmental citizenship among students.